ANALISIS LOSSES AVTUR PADA SARPRAS DPPU SELAMA MASA PANDEMI COVID-19 DI PT. XYZ - Petrina Zipporah (2021)
In March 2020, WHO (World Health Organization) declared that COVID-19 is a global pandemic. According to Badan Pusat Statistik, this pandemic exacerbated the decrease of aircraft passengers, where in April 2020, the domestic aircraft passengers were only 0,85 million passengers. This pandemic impacts the reduction in Avtur demand; meanwhile, the supply can't stop immediately. This incident made PT. XYZ must perform Avtur storage for a long period that impacted the increase of Avtur losses in PT. XYZ. This research analyzed the causative factors of Avtur losses in PT. XYZ during the pandemic with fishbone diagram and pairwise comparisons method. The data was obtained from the interviews and observations. The results of the fishbone diagram obtained 5 categories that causing the Avtur losses. The categories are Methods, Humans, Machines, Materials, and Environment Furthermore, the results of the pairwise comparisons method is the largest weight of the categories that causing Avtur losses is the Environment with a weight of 0,845, which has a sub-category of Solar Heat with a weight of 0,809. Proposed improvements are given by the 5W-1H method to the largest sub-category of each category and evaluation of errors in doing SOP.